2018
DOI: 10.21037/jgo.2018.10.02
|View full text |Cite
|
Sign up to set email alerts
|

Lower lymph node yield following neoadjuvant therapy for rectal cancer has no clinical significance

Abstract: Background: Obtaining 12 lymph nodes following resection for rectal cancer is an important prognostic marker. However, patients who have received neoadjuvant therapy are known to have a lower lymph node yield. We conducted this study to determine the clinical significance of evaluating <12 versus ≥12 lymph nodes in individuals who underwent surgery following neoadjuvant therapy for rectal cancer. Methods: A retrospective analysis of all patients who received neoadjuvant therapy for locally advanced rectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Our multivariate logistic regression demonstrated a best fit prediction model of survival including tumor downstaging, sex, pre-nCRT Hb level, and post-nCRT CEA level. The outcome of our experience was consistent with previous studies (3,4,22). However, contrary to our survival outcome predictor of tumor downstaging, a study in Singapore did not show a survival benefit from tumor downstaging (8).…”
Section: Discussionsupporting
confidence: 90%
“…Our multivariate logistic regression demonstrated a best fit prediction model of survival including tumor downstaging, sex, pre-nCRT Hb level, and post-nCRT CEA level. The outcome of our experience was consistent with previous studies (3,4,22). However, contrary to our survival outcome predictor of tumor downstaging, a study in Singapore did not show a survival benefit from tumor downstaging (8).…”
Section: Discussionsupporting
confidence: 90%
“…Also, our study demonstrated no difference between those with less than 12 lymph nodes and those with more than 12 lymph nodes regarding OS and DFS. These findings are supported by a recent study that demonstrated that though NACRT reduces the lymph nodal yield, it still has no significance on the survival of the patient [30].…”
Section: Discussionsupporting
confidence: 61%
“…Lastly, our results are especially pertinent to our local population, as it allows us to apply these results to patients from a similar background. A recent local paper published by Chan et al demonstrated that the LNH cut-off of 12 had no significant impact on overall survival in patients who received neoadjuvant therapy [22]. Perhaps, a new lower cut-off of 9 can be used in our local population instead.…”
Section: Discussionmentioning
confidence: 99%